ON THE ROLE OF A HEALTHY LIFESTYLE IN WOMEN'S HEALTH - Irmukhamedov , T.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Healthy lifestyle (HLS) is a human activity that is aimed at maintaining and improving the functioning of one's body in accordance with the doctor's recommendations, as well as adapting it to constantly changing environmental conditions. It is also important to achieve the maximum level of health, prevent the occurrence and development of health disorders.